A high-toughness ceramic and its production process
By adding polycarbon methylsilane solution to the SiC whiskers for impregnation and molding, the SiC phase-coated ceramic blank is formed, and carbon boron filling and high-temperature sintering are carried out thereon, the density of SiC ceramics in the prior art is solved. The difficult problem has achieved the preparation of high-toughness and oxidation-resistant ceramics, which are suitable for high-end application fields.
Patent Information
- Application Number
- CN202310941361.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-28
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-07-28
AI Technical Summary
In the prior art, SiC fiber reinforced toughened SiC ceramics are used to affect the performance of the material and the degree of densification is difficult.
Immerse and mold the SiC whiskers by adding polycarbon methylsilane solution to the SiC whiskers to form the SiC phase-coated ceramic blank, and the density is increased through multiple cycles; then carbon-boron filling is added to the SiC phase-coated ceramic blank The solution was vacuum-impregnated and cracked at high temperature to further improve density and oxidation resistance; finally, the carbon-boron-filled ceramic blank was buried in ZrSiO4 powder for high temperature sintering to form high-toughness ceramics.
It effectively improves the toughness of SiC ceramics, improves the density and oxidation resistance of materials, and is suitable for new aviation and nuclear energy systems and other fields.
Smart Images

Figure GDA0005140915010000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic manufacturing, and in particular relates to a high-toughness ceramic and a production process thereof. Background Art
[0002] SiC ceramics have the characteristics of low density, high strength, creep resistance, corrosion resistance and high temperature resistance, and have been widely used in safety protection, thermal protection, machinery and other fields. Fiber-reinforced SiC ceramic-based composites have a series of excellent properties such as high specific strength, high specific modulus, high temperature resistance, and ablation resistance, and have broad application prospects in the fields of aviation and aerospace. For certain specific application parts, materials need to have special functional properties, such as the rotating parts of aircraft engines, and composite materials need to have higher toughness. However, due to the brittleness of the SiC matrix itself, it is not conducive to the weakening and deflection of defects such as cracks when bearing loads.
[0003] Using SiC fiber to reinforce and toughen SiC ceramics is an important way to effectively improve the brittleness of ceramics. The Chinese patent with publication number CN107778019B discloses a method for preparing a silicon carbide whisker reinforced and toughened ceramic matrix composite material, which uses SiC whiskers to toughen SiC ceramic matrix composite materials. However, since SiC whiskers are introduced into the SiC matrix by a simple mechanical mixing method, on the one hand, mechanical mixing has a great influence on the material properties; on the other hand, due to the cross-linking effect between whiskers, it is difficult to densify the composite material. Summary of the invention
[0004] The purpose of the present invention is to provide a high-toughness ceramic and a production process thereof to solve the following technical problems: In the prior art, SiC fiber is used to reinforce and toughen SiC ceramics, which affects material properties and makes densification difficult.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A production process of high-toughness ceramics, comprising the following steps:
[0007] Step 1, adding polycarbomethylsilane solution to SiC whiskers, immersing for 5-10 hours to allow the polycarbomethylsilane solution to completely penetrate the SiC whiskers, filtering, baking at 100°C until semi-dry, and then performing compression molding, drying at 100°C, heating to 1200°C at a rate of 3-5°C / min in a nitrogen atmosphere and keeping the temperature for 1-2 hours, repeating the above operation in step 1 4-6 times to obtain a SiC phase-coated ceramic blank;
[0008] Step 2, adding the carbon-boron filling solution to the SiC phase-coated ceramic blank, placing it in a vacuum drying oven for vacuum impregnation for 1-2 hours, filtering, drying at 100°C, heating to 350-450°C at a rate of 3-5°C / min in a nitrogen atmosphere and keeping warm for 1-2 hours, repeating the above operation in step 2 4-6 times to obtain a carbon-boron filled ceramic blank;
[0009] Step 3: bury the ZrSiO4 powder in the carbon-boron filled ceramic blank, place it in a vacuum reactor, evacuate it to below 10Pa, heat it to 1550-1600℃ at a rate of 6-10℃ / min and keep it warm for 2h, polish the surface after cooling it in the furnace, add liquid nitrogen and freeze it for 15-20s to obtain a high-toughness ceramic;
[0010] The carbon-boron filling solution is prepared by stirring and mixing polycarborane methylsiloxane and xylene in a mass ratio of 60-78:30-32.
[0011] As a further solution of the present invention, the polycarbomethylsilane solution in step 1 is prepared by mixing polycarbomethylsilane and xylene in a mass ratio of 5-10:2-4.
[0012] As a further solution of the present invention, the compression molding pressure in step 1 is 80-140 MPa, and the pressure holding time is 20-30 min.
[0013] As a further solution of the present invention, the vacuum degree of the vacuum drying oven in step 2 is set to -0.1 MPa.
[0014] As a further solution of the present invention, the ZrSiO4 powder is prepared by the following steps: by weight, 45-60 parts of ZrSiO4 powder and 25-30 parts of 75% ethanol solution are mixed and ball milled at a speed of 150-300rpm for 4-6h to obtain ZrSiO4 powder.
[0015] A high-toughness ceramic is prepared by the above production process.
[0016] Beneficial effects of the present invention:
[0017] The invention adds a polycarbomethylsilane solution to a SiC whisker for impregnation, bakes it at 100°C until it is half dry, and then performs compression molding. On the one hand, compared with a method of introducing SiC whiskers into a SiC matrix by a simple mechanical mixing method, the mechanical damage to the SiC whisker is reduced, the influence on the performance of the SiC whisker is reduced, and the toughening effect of the SiC whisker on the ceramic is effectively improved; on the other hand, after the SiC whisker is impregnated with a polycarbomethylsilane solution, high-temperature cracking is performed at 1200°C, SiH and Si-CH3 bonds in the molecule are broken, and SiC with a high specific surface area is formed, which is uniformly and evenly coated on the surface of the silicon carbide whisker, and the polycarbomethylsilane solution is vacuum impregnated and pyrolyzed at 1200°C for 4-6 times to obtain a SiC phase-coated ceramic blank, thereby improving the density of the SiC phase-coated ceramic blank;
[0018] The present invention further performs vacuum impregnation of the SiC phase-coated ceramic blank with a carbon-boron filling solution and pyrolysis at a high temperature of 350-450°C, so that Si-H and Si-CH3 in the polycarborane methylsiloxane molecules in the carbon filling solution are broken, and SiC and carborane C2H2B are further coated. 10 , and obtain the carbon-boron filled ceramic blank, which further improves the density of the carbon-boron filled ceramic blank; and carborane C2H2B 10 It has good high-temperature oxidation resistance. It starts to oxidize at temperatures above 800°C. The oxidation product is B2O3. Under high-temperature conditions, B2O3 is in a molten state with a certain viscosity, forming a protective film to prevent further oxidation of the ceramic matrix. In addition, carborane C2H2B 10 Further filling in the pores on the surface of the ceramic matrix, the elastic deformation of the SiC whiskers squeezes the carborane C2H2B 10 , carborane C2H2B 10 As an energy absorption unit, it absorbs a large amount of energy, thereby improving the surface fracture toughness of the ceramic matrix and preventing the further expansion of surface microcracks. Compared with only coating SiC on the surface of the ceramic matrix, since the SiC ceramic matrix in the micro-regions between the SiC whiskers still retains high brittleness, changes in the external environment can easily lead to microcracks in these micro-regions, and micron-sized SiC fibers are difficult to effectively inhibit the expansion of these microcracks, resulting in a decrease in the toughness of the ceramic.
[0019] The present invention embeds ZrSiO4 powder into a carbon-boron filled ceramic blank and performs high-temperature sintering, wherein ZrSiO4 is cracked to form ZrO2 and molten silicon, and the molten silicon further reacts with residual carbon in the carbon-boron filled ceramic blank to form SiC. After the high-temperature sintering is completed, the ceramic blank is cooled, the surface is polished, and liquid nitrogen is added to freeze for 15-20 seconds, so that the surface of the carbon-boron filled ceramic blank is rapidly cooled, thereby inducing nucleation of ZrO2 monoclinic phase, and further improving the toughening effect on the ceramic.
[0020] In summary, the SiC ceramics prepared by the process of the present invention not only improve the toughness of the ceramics but also achieve anti-oxidation and high densification, and have broad application prospects in the fields of new aviation thermal protection and power systems, new nuclear energy systems, etc. DETAILED DESCRIPTION
[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] Example 1
[0023] A production process of high-toughness ceramics, comprising the following steps:
[0024] Step 1, add polycarbomethylsilane solution (polycarbomethylsilane and xylene are mixed in a mass ratio of 5:4) to the SiC whisker, immerse for 5-10 hours to allow the polycarbomethylsilane solution to completely penetrate the SiC whisker, filter, bake at 100°C until semi-dry, and then perform compression molding (the compression molding pressure is 800MPa, and the holding time is 20min), dry at 100°C, heat to 1200°C at a rate of 3°C / min in a nitrogen atmosphere and keep warm for 1h, repeat the above operation in step 1 4 times to obtain a SiC phase-coated ceramic blank;
[0025] Step 2: add the carbon-boron filling solution to the SiC phase-coated ceramic blank, place it in a vacuum drying oven (vacuum degree set to -0.1MPa) for vacuum impregnation for 1 hour, filter, dry at 100°C, heat to 350°C at a rate of 3°C / min in a nitrogen atmosphere and keep warm for 1-2 hours, repeat the above operation in step 2 4 times to obtain a carbon-boron filled ceramic blank;
[0026] Step 3: Mix 45 parts of ZrSiO4 powder and 25 parts of 75% ethanol solution by volume, and ball-mill them at a speed of 150 rpm / min for 4 hours to obtain ZrSiO4 powder;
[0027] The carbon-boron filled ceramic blank is buried in ZrSiO4 powder, placed in a vacuum reactor, evacuated to below 10Pa, heated to 1550℃ at a rate of 6℃ / min and kept warm for 2h, surface polished after furnace cooling, and frozen with liquid nitrogen for 15s to obtain a high-toughness ceramic.
[0028] Example 2
[0029] A production process of high-toughness ceramics, comprising the following steps:
[0030] Step 1, add polycarbomethylsilane solution (polycarbomethylsilane and xylene are mixed in a mass ratio of 10:2) to the SiC whisker, immerse for 10 hours to allow the polycarbomethylsilane solution to completely penetrate the SiC whisker, filter, bake at 100°C until semi-dry, and then perform compression molding (the compression molding pressure is 140MPa, and the holding time is 30min), dry at 100°C, heat to 1200°C at a rate of 5°C / min in a nitrogen atmosphere and keep warm for 2h, repeat the above operation in step 1 6 times to obtain a SiC phase-coated ceramic blank;
[0031] Step 2: add the carbon-boron filling solution to the SiC phase-coated ceramic blank, place it in a vacuum drying oven (vacuum degree set to -0.1 MPa) for vacuum impregnation for 2 hours, filter, dry at 100°C, heat to 450°C at a rate of 5°C / min in a nitrogen atmosphere and keep warm for 2 hours, repeat the above operation in step 2 6 times to obtain a carbon-boron filled ceramic blank;
[0032] Step 3: Mix 60 parts of ZrSiO4 powder and 30 parts of 75% ethanol solution by volume, and ball-mill at a speed of 300 rpm / min for 4-6 hours to obtain ZrSiO4 powder;
[0033] The carbon-boron filled ceramic blank is buried in ZrSiO4 powder, placed in a vacuum reactor, evacuated to below 10Pa, heated to 1600℃ at a rate of 10℃ / min and kept warm for 2h, surface polished after furnace cooling, and frozen with liquid nitrogen for 20s to obtain a high-toughness ceramic.
[0034] Comparative Example 1
[0035] A production process of high-toughness ceramics, comprising the following steps:
[0036] Step 1, add the carbon-boron filling solution to the SiC whisker, place it in a vacuum drying oven (vacuum degree is set to -0.1MPa) for vacuum impregnation for 1 hour, filter, dry at 100°C, heat to 350°C at a rate of 3°C / min in a nitrogen atmosphere and keep warm for 1-2 hours, repeat the above operation in step 2 4 times to obtain a carbon-boron filled ceramic blank;
[0037] Step 2, by mass, 45 parts of ZrSiO4 powder and 25 parts of 75% ethanol solution were mixed and ball-milled at a speed of 150 rpm / min for 4 hours to obtain ZrSiO4 powder;
[0038] The carbon-boron filled ceramic blank is buried in ZrSiO4 powder, placed in a vacuum reactor, evacuated to below 10Pa, heated to 1550℃ at a rate of 6℃ / min and kept warm for 2h, surface polished after furnace cooling, and frozen with liquid nitrogen for 15s to obtain a high-toughness ceramic.
[0039] Compared with Example 1, this comparative example omits step 1, and the remaining steps and parameters are the same.
[0040] Comparative Example 2
[0041] A production process of high-toughness ceramics, comprising the following steps:
[0042] Step 1, add polycarbomethylsilane solution (polycarbomethylsilane and xylene are mixed in a mass ratio of 5:4) to SiC whiskers, immerse for 5-10 hours to allow the polycarbomethylsilane solution to completely penetrate the SiC whiskers, filter, bake at 100°C until semi-dry, and then perform compression molding (the compression molding pressure is 800MPa, and the holding time is 20min), dry at 100°C, heat to 1200°C at a rate of 3°C / min in a nitrogen atmosphere and keep warm for 1h, repeat the above operation in step 1 4 times, and obtain a SiC phase-coated ceramic blank;
[0043] Step 2, by mass, 45 parts of ZrSiO4 powder and 25 parts of 75% ethanol solution were mixed and ball-milled at a speed of 150 rpm / min for 4 hours to obtain ZrSiO4 powder;
[0044] The SiC phase-coated ceramic blank is buried in ZrSiO4 powder, placed in a vacuum reactor, evacuated to below 10Pa, heated to 1550℃ at a rate of 6℃ / min and kept warm for 2h, surface polished after furnace cooling, and frozen with liquid nitrogen for 15s to obtain a high-toughness ceramic.
[0045] Compared with Example 1, this comparative example omits step 2, and the remaining steps and parameters are the same.
[0046] Comparative Example 3
[0047] A production process of high-toughness ceramics, comprising the following steps:
[0048] Step 1, add polycarbomethylsilane solution (polycarbomethylsilane and xylene are mixed in a mass ratio of 5:4) to SiC whiskers, immerse for 5-10 hours to allow the polycarbomethylsilane solution to completely penetrate the SiC whiskers, filter, bake at 100°C until semi-dry, and then perform compression molding (the compression molding pressure is 800MPa, and the holding time is 20min), dry at 100°C, heat to 1200°C at a rate of 3°C / min in a nitrogen atmosphere and keep warm for 1h, repeat the above operation in step 1 4 times, and obtain a SiC phase-coated ceramic blank;
[0049] Step 2, add the carbon-boron filling solution to the SiC phase-coated ceramic blank, place it in a vacuum drying oven (vacuum degree set to -0.1MPa) for vacuum impregnation for 1 hour, filter, dry at 100°C, heat to 350°C at a rate of 3°C / min in a nitrogen atmosphere and keep warm for 1-2 hours, repeat the above operation in step 2 4 times to obtain a carbon-boron filled ceramic blank;
[0050] Step 3: After cooling the carbon-boron filled ceramic blank in the furnace, the surface is polished, and liquid nitrogen is added to freeze the blank for 15 seconds to obtain a high-toughness ceramic.
[0051] Compared with Example 1, the present comparative example omits step 3 of "burying the carbon-boron filled ceramic blank in ZrSiO4 powder, placing it in a vacuum reactor, evacuating it to below 10Pa, heating it to 1600°C at a rate of 10°C / min and keeping it warm for 2h", and the remaining steps and parameters are the same.
[0052] Comparative Example 4
[0053] A production process of high-toughness ceramics, comprising the following steps:
[0054] Step 1, add polycarbomethylsilane solution (polycarbomethylsilane and xylene are mixed in a mass ratio of 5:4) to the SiC whisker, immerse for 5-10 hours to allow the polycarbomethylsilane solution to completely penetrate the SiC whisker, filter, bake at 100°C until semi-dry, and then perform compression molding (the compression molding pressure is 800MPa, and the holding time is 20min), dry at 100°C, heat to 1200°C at a rate of 3°C / min in a nitrogen atmosphere and keep warm for 1h, repeat the above operation in step 1 4 times to obtain a SiC phase-coated ceramic blank;
[0055] Step 2: add the carbon-boron filling solution to the SiC phase-coated ceramic blank, place it in a vacuum drying oven (vacuum degree set to -0.1MPa) for vacuum impregnation for 1 hour, filter, dry at 100°C, heat to 350°C at a rate of 3°C / min in a nitrogen atmosphere and keep warm for 1-2 hours, repeat the above operation in step 2 4 times to obtain a carbon-boron filled ceramic blank;
[0056] Step 3: Mix 45 parts of ZrSiO4 powder and 25 parts of 75% ethanol solution by volume, and ball-mill them at a speed of 150 rpm / min for 4 hours to obtain ZrSiO4 powder;
[0057] The carbon-boron filled ceramic blank is buried in ZrSiO4 powder, placed in a vacuum reactor, evacuated to below 10Pa, heated to 1550℃ at a rate of 6℃ / min and kept warm for 2h, and then surface polished after cooling in the furnace to obtain a high-toughness ceramic.
[0058] Compared with Example 1, the comparative example omits the step 3 of "adding liquid nitrogen and freezing for 15 seconds", and the remaining steps and parameters are the same.
[0059] The performance of a high-toughness ceramic obtained in Example 1-2 and Comparative Example 1-4 was tested:
[0060] (1) Fracture toughness test according to ASTM C1421-10, unit: MPa;
[0061] (2) Anti-oxidation test was carried out according to JC / T 2530-2019. Experimental conditions: 1400℃ constant temperature for 60h. The mass change before and after oxidation was tested. Unit: g / cm 3 ;
[0062] (3) Test the apparent porosity according to GB / T 25995-2010;
[0063] The test results are shown in Table 1;
[0064] Table 1
[0065]
[0066] It can be seen from Table 1 that the high-toughness ceramic prepared in Example 1-2 has higher toughness, oxidation resistance and higher density than the high-toughness ceramic prepared in Comparative Example 1-4.
[0067] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0068] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A production process for high-toughness ceramics, characterized in that: The steps include: Step 1, adding polycarbomethylsilane solution to SiC whiskers, immersing for 5-10 hours, filtering, drying at 100°C until semi-dry, and then compression molding, drying at 100°C, heating to 1200°C at a rate of 3-5°C / min in a nitrogen atmosphere and keeping the temperature for 1-2 hours; Wherein, the polycarbomethylsilane solution is prepared by mixing polycarbomethylsilane and xylene in a mass ratio of 5-10:2-4; Step 2, repeat step 1 4-6 times to obtain a SiC phase coated ceramic blank; Step 3, adding carbon-boron filling solution to the SiC phase coated ceramic blank, placing it in a vacuum drying oven for vacuum impregnation for 1-2 hours, filtering, drying at 100°C, heating to 350-450°C at a rate of 3-5°C / min in a nitrogen atmosphere and keeping it warm for 1-2 hours; Step 4: Repeat step 3 4-6 times to obtain a carbon-boron filled ceramic blank; Step 5: bury the carbon-boron filled ceramic blank in ZrSiO4 powder, place it in a vacuum reactor, evacuate to below 10Pa, heat to 1550-1600℃ at a rate of 6-10℃ / min and keep warm for 2h, polish the surface after cooling in the furnace, add liquid nitrogen and freeze for 15-20s to obtain a high-toughness ceramic; The carbon-boron filling solution is prepared by stirring and mixing polycarborane methylsiloxane and xylene in a mass ratio of 60-78:30-32.
2. A production process for high-toughness ceramics according to claim 1, characterized in that: The compression molding pressure is 80-140 MPa, and the pressure holding time is 20-30 min.
3. The production process of a high-toughness ceramic according to claim 1, characterized in that: The vacuum degree of the vacuum drying oven in step 3 is set to -0.1 MPa.
4. The production process of a high-toughness ceramic according to claim 1, characterized in that: The ZrSiO4 powder is prepared by the following steps: by weight, 45-60 parts of ZrSiO4 powder and 25-30 parts of 75% ethanol solution are mixed and ball-milled at a speed of 150-300 rpm for 4-6 hours to obtain ZrSiO4 powder.
5. A high toughness ceramic, characterized in that: The invention is prepared by the production process described in any one of claims 1 to 4.
Citation Information
Patent Citations
A method for preparing silicon carbide whisker-reinforced and toughened ceramic matrix composites
CN107778019B
ZrSiO4-SiC porous ceramics and preparation method thereof
CN105753501A
Preparation method of ZrC ceramic material surface ZrB2-SiC composite coating
CN107056334A